2017
DOI: 10.1007/s13524-017-0592-0
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Intentions and Residential Relocations

Abstract: This research addresses the question of whether fertility intentions (before conception) are associated with residential relocations and the distance of the relocation. We empirically tested this using data from two birth cohorts (aged 24-28 and 34-38 in the first survey wave) of the German Family Panel (pairfam) and event history analysis. Bivariate analyses showed that coupled individuals relocated at a higher rate if they intended to have a(nother) child. We found substantial heterogeneity according to indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 50 publications
2
37
0
1
Order By: Relevance
“…Family formation is closely related to both residential mobility and first-time homeownership (Enström Öst, 2012;Feijten & Mulder, 2002;Mulder & Lauster, 2010;Mulder & Wagner, 2001). Consistent with the view that relocations are instrumental means for reaching life course goals, like starting a family, moves in young adulthood often take place in anticipation of marriage and childbirth (Bayrakdar et al, 2018;Kley, 2011;Kulu, 2008;Kulu & Steele, 2013;Kurz, 2004b;Michielin & Mulder, 2008;Mulder & Wagner, 1998;Vidal, Huinink, & Feldhaus, 2017;Wagner & Mulder, 2015;Willekens, 1987). 2 Homeownership rates have increased since 1980 in Germany but are still below those of Great Britain, the Netherlands, and other European countries (Filandri & Olagnero, 2014;Wind, Lersch, & Dewilde, 2017).…”
Section: Housing Careers: Empirical Findingsmentioning
confidence: 89%
“…Family formation is closely related to both residential mobility and first-time homeownership (Enström Öst, 2012;Feijten & Mulder, 2002;Mulder & Lauster, 2010;Mulder & Wagner, 2001). Consistent with the view that relocations are instrumental means for reaching life course goals, like starting a family, moves in young adulthood often take place in anticipation of marriage and childbirth (Bayrakdar et al, 2018;Kley, 2011;Kulu, 2008;Kulu & Steele, 2013;Kurz, 2004b;Michielin & Mulder, 2008;Mulder & Wagner, 1998;Vidal, Huinink, & Feldhaus, 2017;Wagner & Mulder, 2015;Willekens, 1987). 2 Homeownership rates have increased since 1980 in Germany but are still below those of Great Britain, the Netherlands, and other European countries (Filandri & Olagnero, 2014;Wind, Lersch, & Dewilde, 2017).…”
Section: Housing Careers: Empirical Findingsmentioning
confidence: 89%
“…Lacking direct measures on fertility intentions or expectations, previous studies on anticipatory moves may find it diffi- They found that expecting to have a child in the future increases the likelihood of moving by 0.036. Vidal et al (2017) examined the effect of fertility intention, measured dichotomously, on relocations within town, over short distances and over long distances using the German Family Panel for the period 2008-2013. They found that rates of relocations are positively correlated with fertility intentions, but the association becomes statistically insignificant once age and parental status are controlled for.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has established the connection between changes in housing and childbirth (Feijten & Mulder, 2002;Kulu, Boyle, & Andersson, 2009;Kulu & Vikat, 2008;Kulu, Vikat, & Andersson, 2007;Mulder & Wagner, 1998, 2001Murphy & Sullivan, 1985) and acknowledged the complexity and simultaneity of housing and fertility events (Clark, 2012;Kulu & Steele, 2013;Michielin & Mulder, 2008;Öst, 2012). Due to the lack of information on fertility intentions, these studies utilise the timing of actual births to indirectly capture fertility intentions at the prior stage of family planning (Ermisch & Steele, 2016;Öst, 2012); and thus, they fail to address the potential impact of intentions in one life domain on actual behaviour in another (Vidal, Huinink, & Feldhaus, 2017). There is also a lack of studies into the role of housing contexts in the realisation of childbearing intentions.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent literature on migration and residential mobility, it is often stressed that the moving decisions of individuals are best understood from a life course perspective, as at each life stage events in various life domains can trigger or prevent moves (Findlay, McCollum, Coulter, & Gayle, 2015;Geist & McManus, 2008;Kley, 2011;Rossi, 1955). The number of empirical studies that have taken such a life course perspective has increased substantially in recent years (e.g., Coulter & Scott, 2015;De Groot, Mulder, Das, & Manting, 2011;De Jong & Graefe, 2008;Falkingham, Sage, Stone, & Vlachantoni, 2016;Kulu, 2008; Thomas, Stillwell, & Gould, 2016;Vidal, Huinink, & Feldhaus, 2017). At the same time, longitudinal life course research has made important strides in integrating both moving intentions and moving events into comprehensive analyses (e.g., Clark & Lisowski, 2018; De Groot, Mulder, Das, et al, 2011;Kley, 2011;Lu, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when co-residing couples split up, one of the partners tends to move out quickly, whereas the second partner is also at greater risk of moving (De Groot, Mulder, Das, et al, 2011). Fertility intentions or the birth of a(nother) child might incentivise a couple to move to a larger home (Vidal et al, 2017). The characteristics of the neighbourhood, such as the quality of its schools and its safety levels, might be relevant in the early family phase in particular (see also Clark & Ledwith, 2006;Huinink & Kley, 2008;Landale & Guest, 1985).…”
Section: Introductionmentioning
confidence: 99%